Pengembangan Strategi Pemasaran UMKM Dapur Tihwa Pada Masa Pandemi Covid-19 - Hartini Halim, Imelda; Naufal Aqilla Sukmana, Ariq; Victoria, Benedicta; Vinsky, Elvin; Christopher, Jessica; Wijaya, Meryssa; Jonathan Rorong, Raynard; Ginting, Maydison (Journal Pemberdayaan Masyarakat Indonesia, 2022)
During the Covid-19 pandemic, lots of businesses were negatively affected, one of which is Dapur Tihwa, a Small Medium Enterprises (SME) around Cianjur which sells various types of food such as cireng and seblak. Not only external challenges such as the pandemic period which resulted in Dapur Tihwa decreased sales up to 50%, there's many internal problems experienced by Dapur Tihwa such as production, finance, marketing, distribution, and mindset. In fact, as we all know, Small Medium Enterprises (SME) have a major contribution due to Indonesia's macro economy. Therefore, during the community development opportunity held by Universitas Prasetiya Mulya and based on the analysis that has been carried out by the group, the group will focusing on conducting research especially in the marketing department by improving Dapur Tihwa marketing strategy with the intention to increase affected sales during this Covid-19 pandemic. Through intensive assistance, our partner has succeeded in obtaining new, more attractive packaging stickers, knowledge in digital technology, as well as the addition of marketing and sales media, namely Shopee and Tokopedia.